2014
DOI: 10.1007/s11104-014-2251-1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in coupling of kinetics and molecular scale tools to shed light on soil biogeochemical processes

Abstract: Background Biogeochemical processes in soils such as sorption, precipitation, and redox play critical roles in the cycling and fate of nutrients, metal(loid)s and organic chemicals in soil and water environments. Advanced analytical tools enable soil scientists to track these processes in real-time and at the molecular scale. Scope This review focuses on recent research that has employed state-of-the-art molecular scale spectroscopy, coupled with kinetics, to elucidate the mechanisms of nutrient and metal(loid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 89 publications
(105 reference statements)
0
10
0
Order By: Relevance
“…The negative impact of AB‐DTPA on cumulative Ni uptake may be due to the nature of the Ni mineral phases. Sparks (2015) indicates that Ni forms an inner‐sphere complex at low surface‐covering rates and a Ni‐Al hydroxide precipitates at higher coverage. Thus, possibly Ni was influenced to a greater degree by organo‐mineral surface complexation and not by precipitation reactions governed by soil pH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative impact of AB‐DTPA on cumulative Ni uptake may be due to the nature of the Ni mineral phases. Sparks (2015) indicates that Ni forms an inner‐sphere complex at low surface‐covering rates and a Ni‐Al hydroxide precipitates at higher coverage. Thus, possibly Ni was influenced to a greater degree by organo‐mineral surface complexation and not by precipitation reactions governed by soil pH.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses of variance and path analyses will be used to determine the impact of biosolids applications, AB‐DTPA concentrations, pH, and organic C and serve as basis for testing the hypothesis. Lindsay (1979) detailed the pH effects on P and micronutrient availability, whereas Sparks (2015) used molecular scale tools to better delineate mineral effects on plant availability that may supersede pH effects. Richards et al (2011) found that changes in soil organic matter content associated with biosolids applications also affected P and micronutrient availability.…”
mentioning
confidence: 99%
“…While biogeochemical cycles logically interact with each other, they are generally studied in isolation. Theoretical coupling among soil biogeochemical cycles can be inferred from thermodynamic modeling [ 6 ], as well as some field evidence. For example, methane oxidation is linked with N cycling [ 7 ], C utilization rates vary with P bioavailability [ 8 ], and ammonia oxidation couples with ferric reduction or thiosulfate reduction under anaerobic conditions [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, methane oxidation is linked with N cycling [ 7 ], C utilization rates vary with P bioavailability [ 8 ], and ammonia oxidation couples with ferric reduction or thiosulfate reduction under anaerobic conditions [ 9 , 10 ]. However, the coupling of some biogeochemical cycles is predicted to exist only on a thermodynamics basis [ 6 ]. Moreover, in all these approaches, there is little information concerning the specific microbes regulating the coupling of biogeochemical cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive investigations have been conducted into the adsorption of heavy metals by soils and soil constituents such as clay minerals234, iron and aluminum oxides5, and organic matter67. Electrostatic adsorption, specific adsorption and surface precipitation were main mechanisms for the adsorption of heavy metals by soils89. Neutral salt such as KNO 3 was used to extract the heavy metals adsorbed by soils electrostatically through cation exchange reaction10.…”
mentioning
confidence: 99%